2007
DOI: 10.1111/j.1582-4934.2007.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of human mesenchymal stem cells to epithelial lineage

Abstract: Our study examined whether human bone marrow-derived MSCs are able to differentiate, in vitro, into functional epithelial-like cells. MSCs were isolated from the sternum of 8 patients with different hematological disorders. The surface phenotype of these cells was characterized.To induce epithelial differentiation, MSCs were cultured using Epidermal Growth Factor, Keratinocyte Growth Factor, Hepatocyte Growth Factor and Insulin-like growth Factor-II. Differentiated cells were further characterized both morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 28 publications
4
106
0
1
Order By: Relevance
“…18 For example, the propensity of stromal cell populations to promote tissue healing has been shown in the settings of lung, brain, heart, and kidney injury. [19][20][21][22] It has also been shown that cells in the marrow are capable of differentiation into the epithelial lineage 23,24 and that after hematopoietic cell transplantation these cells are able to engraft in the skin of the recipient, especially in sites affected by graft-versus-host disease. 25 Finally, directly or systemically administered BM cells have been shown to promote healing of skin wounds, 26,27 which are the hallmark of RDEB.…”
Section: Introductionmentioning
confidence: 99%
“…18 For example, the propensity of stromal cell populations to promote tissue healing has been shown in the settings of lung, brain, heart, and kidney injury. [19][20][21][22] It has also been shown that cells in the marrow are capable of differentiation into the epithelial lineage 23,24 and that after hematopoietic cell transplantation these cells are able to engraft in the skin of the recipient, especially in sites affected by graft-versus-host disease. 25 Finally, directly or systemically administered BM cells have been shown to promote healing of skin wounds, 26,27 which are the hallmark of RDEB.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have also been significant advances in the use of autologous mesenchymal stem cells to regenerate human tissues [28,29]. It has been reported that MSC express markers pertaining to corneal epithelial stem cells [30][31][32][33] and can be induced to differentiate to epithelial like cells both in vitro and in vivo [33][34][35][36]. A critical factor in mesenchymal stem cell biology is to propagate cells with suitable stem cell characteristics, multipotency and high proliferative potential for its use in various biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…First, MSCs are able to differentiate toward fibroblasts, endothelial cells, and keratinocytes. 45,46 However, accumulating evidence suggests that MSCs are recruited and mobilized from distant sites toward the wound. Injury per se increases the levels of circulating MSCs in peripheral circulation.…”
Section: Mscs In Skin and During Wound Healingmentioning
confidence: 99%